1988
DOI: 10.1073/pnas.85.4.1043
|View full text |Cite
|
Sign up to set email alerts
|

Illegitimate recombination induced by benzo[a]pyrene diol epoxide in Escherichia coli.

Abstract: Duplex DNA oligomer constructs (32 base pairs) were prepared that contained a single benzo[alpyrene (BP) adduct at a specific deoxyadenosine or deoxyguanosine site in either one or both strands. These constructs were inserted into M13 replicative form viral DNA, and the DNA from progeny virus generated by transfection of Escherichia coli was examined by sequence analysis at the site of oligomer insertion. With nonalkylated constructs, and with constructs containing only one BP adduct, no sequence alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In lieu of a homologous template, the collapsed fork invades an active replication fork within physical proximity using the microhomology as a primer. This hypothesis is supported by previous observations using a bacterial model investigating BPDE adducts 43 . Specifically, DNA segments containing BPDE adducts were more likely to be deleted or replaced with an alternative sequence (>42 bp) than segments without adducts (no alterations observed).…”
Section: Resultssupporting
confidence: 89%
“…In lieu of a homologous template, the collapsed fork invades an active replication fork within physical proximity using the microhomology as a primer. This hypothesis is supported by previous observations using a bacterial model investigating BPDE adducts 43 . Specifically, DNA segments containing BPDE adducts were more likely to be deleted or replaced with an alternative sequence (>42 bp) than segments without adducts (no alterations observed).…”
Section: Resultssupporting
confidence: 89%
“…Nuclear magnetic resonance studies have demonstrated that two closely opposed furans distort the DNA structure (37) and DNA fragments with a nick or nucleotide gap have increased flexibility and a V-shaped structure (38;39). Previously Kokontis et al (40) proposed that distortion of the DNA structure by two closely opposed benzo[a]pyrene diol epoxide lesions activated recombination resulting in an enhancement of deletion frequency. The recF recombination pathway has also been implicated in cell death and has been proposed to increase DSB formation during thymine-less death (41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that irradiation of Drosophila melanogaster organisms with X rays induces chromosomal aberrations (16). Treatment of bacteria with UV light and other DNA-damaging agents enhanced various kinds of DNA rearrangements (9,12,17,21). However, the mechanisms of illegitimate recombination enhanced by DNA-damaging agents is not yet understood.…”
mentioning
confidence: 99%